2017
DOI: 10.1002/jez.2149
|View full text |Cite
|
Sign up to set email alerts
|

Identification of warm temperature acclimation‐associated 65‐kDa protein‐2 in Kumgang fat minnow Rhynchocypris kumgangensis

Abstract: Warm temperature acclimation-associated 65-kDa protein (Wap65) is known to respond to elevated water temperatures and the corresponding gene from several fish species has been cloned. Expression of Wap65 gene is induced by various physiological stresses, such as increase in water temperature, immune response and heavy metal exposure. Two isolated Wap65 genes, Wap65-1 and Wap65-2, display distinct tissue distribution and physiological functions despite high sequence homology. In a previous study, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…This phenomenon suggests a similar mechanism of thermal acclimation within the testis and liver in carp. Our findings on the preferential induction of Wap65-1 during thermal acclimation collaborate previous observations in other fish species [19,20,22,25], but the mechanism of Wap65 action during acclimation is unknown. Weber et al [52] indicated that the warm acclimation response in fish involves increases in erythrocyte numbers and total hemoglobin content.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This phenomenon suggests a similar mechanism of thermal acclimation within the testis and liver in carp. Our findings on the preferential induction of Wap65-1 during thermal acclimation collaborate previous observations in other fish species [19,20,22,25], but the mechanism of Wap65 action during acclimation is unknown. Weber et al [52] indicated that the warm acclimation response in fish involves increases in erythrocyte numbers and total hemoglobin content.…”
Section: Discussionsupporting
confidence: 90%
“…These data indicate the specificity of Wap65-2 to bacterial infection and inflammation within the testis, contrary to Wap65-1, which seems to be specific for temperature acclimation (see above). The involvement of Wap65-2 in the response to bacteria concurs with transcriptional control of Wap65-2 by factors derived from the immune system such as cytokines, e.g., IL-1 involved in induction of acute phase proteins, including Wap65 [25]. Analysis of the 5′ flanking region of carp Wap65 genes indicated the presence of more cytokine responsive elements and binding sites for transcription factors associated with immune response such as STAT, CEBP, TATABox, AP1, HNF, HSF, OCT1, IRF1, IRF2, CREBP for Wap65-2 as compared to Wap65-1 (Additional files 1, 9).…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Hemopexin also associates with high density lipoproteins (HDL), influencing their inflammatory properties (Mehta and Reddy, 2015). In relation to aquatic animals, hemopexin has been associated with physiological stresses, including increased water temperature, immune response and heavy metal exposure in fish (Kwon and Ghil, 2017;Diaz-Rosales et al, 2014).…”
Section: Discussionmentioning
confidence: 99%